Pro-apoptotic and size-reducing effects of protein corona-modulating nano-architectures enclosing platinum prodrug in in vivo oral carcinoma. (7th September 2022) - Mapanao, Ana Katrina; Sarogni, Patrizia; Santi, Melissa; Menicagli, Michele; Gonnelli, Alessandra; Zamborlin, Agata; Ermini, Maria Laura; Voliani, Valerio
Abstract : A protein corona-modulating peptide is integrated with non-persistent plasmonic nano-architectures containing a cisplatin prodrug to improve the efficacy of the nanomaterial-mediated chemotherapy in alternative in vivo models of oral carcinoma. Abstract : The selective and localized delivery of active agents to neoplasms is crucial to enhance the chemotherapeutic efficacy while reducing the associated side effects. The encapsulation of chemotherapeutics in nanoparticles decorated with targeting agents is a strategy of special interest to improve drug delivery. However, serum protein adsorption often compromises the in vivo efficiency of targeting agents, leading to protein corona formation that interferes with the targeting process. Here, the enhanced efficacy of hybrid nano-architectures enclosing a platinum prodrug and decorated with a customized peptide (NAs-cisPt-Tf2) is demonstrated by employing alternative in vivo models of oral carcinoma. The peptide binds to transferrin and modulates the protein corona formation on NAs-cisPt-Tf2, supporting the identification of its receptor. Optimized chorioallantoic membrane cancer models (CAMs) enabled a thorough assessment of the tumor-suppressing effect of NAs-cisPt-Tf2 as well as the quantitative evaluation of angiogenesis and cell cycle associated mechanisms. The treatment strategy resulted in a significant tumor volume reduction coupled with anti-angiogenic and pro-apoptotic effects inferred from the downregulation of the vascular endothelial growth factor gene and increased expression of cleaved caspase-3. Overall, this study provides a potentially effective tumor-targeted approach for a non-invasive management of oral carcinoma.